Characterization and crystal structure of prolyl endopeptidase from abalone (Haliotis discus hannai). (15th December 2020) - Li, Wan-Yu; Li, Yue; Chen, Yu-Lei; Hu, Jian-Jian; Mengist, Hylemariam Mihiretie; Liu, Guang-Ming; Jin, Tengchuan; Cao, Min-Jie
Highlights: A recombinant prolyl endopeptidase from Haliotis discus hannai (Hdh-PEP) was prepared. The optimum pH and temperature of rHdh-PEP was 6 and 20 °C. The crystal structure of rHdh-PEP was determined. rHdh-PEP specifically cleaved collagen peptides at the C-terminal of proline residues. Abstract: Aimed to study the characteristics of prolyl endopeptidase (PEP, EC 3.4.21.26) and its possible role in the degradation of collagen, we cloned the full-length cDNA sequence of PEP from abalone ( Haliotis discus hannai ) (Hdh-PEP). Recombinant Hdh-PEP (rHdh-PEP) was expressed in vitro, its enzymatic properties were detected, and its secondary structure was analyzed by Circular Dichroism (CD). We for the first time determined the 1.5 Å crystal structure of rHdh-PEP. The decomposition effect of rHdh-PEP on collagen peptides was analyzed. Our data revealed that the molecular weight of rHdh-PEP is 85 kDa, consisting of a catalytic domain and a β-propeller domain. The optimal pH and temperature of rHdh-PEP were pH 6.0 and 20 °C, respectively. Using small collagen peptides as substrates, HPLC-ESI-MS analysis confirmed that rHdh-PEP specifically cleaved at the carboxyl side of proline residues, suggesting its role in the degradation of collagen peptides during autolysis.